Impaired Attentional Control in Pedophiles in a Sexual Distractor Task - Jordan, Kirsten; Fromberger, Peter; von Herder, Jakob; Steinkrauss, Henrike; Nemetschek, Rebekka; Witzel, Joachim; Müller, Jürgen L. (Frontiers in Psychiatry, 2016)
Pedophilic disorder, a subtype of paraphilia, is defined as a recurrent sexual interest in prepubescent children, which is characterized by persistent thoughts, fantasies, urges, sexual arousal or behavior. Besides a deviant sexual preference, sexual preoccupation was found to be a dynamic risk factor for reoffending. Thus, it is conceivable that sex offenders and especially sex offenders against children have difficulties to control their responses to sexual stimuli. In the current study pedophiles, forensic and non-forensic control subjects had to solve a cognitive task while sexual distractors were presented simultaneously. This kind of task also requires control functions. Therefore, data was analyzed with respect to attentional control while comparing eye movements towards sexual distractors and towards the cognitive task. We were mainly interested in how early (fixation latency) and late (relative fixation time) attentional processes were allocated to both, the cognitive target stimuli and the sexual distractors. Pedophiles demonstrated significantly lower attentional control in the sexual distractor task than both control groups (non-pedophiles). They showed a shorter fixation latency and longer fixation time for sexual distractors than non-pedophiles. Furthermore, pedophiles demonstrated a longer fixation latency and shorter fixation time for cognitive target stimuli. For classification analyses, an attention control index (ACI) was built, i.e. the difference between eye movements on cognitive target stimuli and sexual distractors. For the ACI of early attentional processes, i.e. fixation latency, a good classification between pedophiles and non-pedophiles was found. We assumed that the measured attentional control represents inhibitory executive functions, specifically interference control. Further studies should examine if low attentional control in pedophiles is due to low motivation to solve the task or rather to a lack of ability to control attention with respect to sexual and/or neutral distractors. Prospectively, this design could be useful to generate hypotheses about clinical important aspects of controllability, the capacity of self-control and the severity of a paraphilic disorder.